Hubungan Terpaan Berita Covid-19 Di Media Massa Dan Tingkat Kecemasan Dengan Perilaku Hidup Bersih Dan Sehat Pada Remaja - Muhammad Rizki Nugraha; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
At the beginning of 2020, the World Health Organization (WHO) stated that the world condition is currently very threatened by the emergence of a new outbreak, namely COVID-19 due to the spread of the Corona Virus so fast that it has infected all countries around the world. The development of COVID-19 information that tends to be negative has never escaped the coverage of all the mass media so that it gives enough anxiety in the midst of people's lives, especially for adolescents with unstable mental conditions. This has led to an intention for the government to make policies for the community in an effort to reduce the number of cases as well as a form of preventive action with the obligation to comply with health protocols with PHBS indicators that have been made by the Indonesian Ministry of Health. This study aims to determine the relationship between news exposure COVID-19 in Mass Media and Anxiety Levels with Clean and Healthy Living Behaviors in Adolescents, using the Non-Probability Sampling technique in the form of Quota Sampling with a total sample of 60 teenage respondents with the provisions being 15-24 years old in Semarang City, and consuming news COVID-19 in the last three months. The type of research used is explanatory, and this research uses the Theory of Dependence on the Effects of Mass Communication and the Theory of Motivation Protection. The results showed that there was no relationship between COVID-19 News Exposure in Mass Media with Clean and Healthy Living Behavior in Adolescents. This was obtained from the results of Kendall's Tau_b correlation analysis test which showed a significance value of 0.531 and a coefficient value of -0.059 It was concluded that the mass media provided little knowledge or cognitive effects but had not yet reached the decision and attitude stage. Besides, there is also no relationship between Anxiety Levels and a Clean and Healthy Lifestyle in Adolescents. This is obtained from the test results of Kendall's Tau_b correlation analysis which shows a significance value of 0.148 and a coefficient value of 0.139 so that it can be concluded that the respondent's behavior in daily life is not influenced by feelings of anxiety that the respondent has.